Antioksidan Ekstrak Etanol Daun Pedada (Sonneratia ovata Backer) - Raharjo, Danang; Fitriawati, Anna; Aminulloh, Muhammad (LPPM Universitas Duta Bangsa Surakarta, 2024)
Free radicals are reactive oxygen compounds that are known to be compounds that have free or unpaired electrons. Free radicals will look for new partners so that they will easily bind to other substances such as proteins, fats, and DNA in the body, resulting in cell damage and causing various degenerative diseases. To overcome the negative effects of free radicals, a substance that acts as an antioxidant is needed. Sonneratia Ovata or often called pedada by coastal communities is often used to treat various diseases including diabetes, ulcers, analgesic diarrhea, inflammation, pain and accelerate wound healing. This study aims to examine the levels of flavonoid compounds in the ethanol extract of S. ovata leaves using the colorimetric method and antioxidant activity using the ABTS method (2,2 azinobis (3-ethylbenzothiazolin-6- sulfonic acid) and DPPH (2,2-diphenyl-1-picrylhydrazyl) on the ethanol extract of S. ovata leaves. The research process began with the extraction of S. ovata leaves with 96% ethanol, followed by determination of total flavonoid levels and antioxidant testing. From the results of the determination of total flavonoid levels, it was found that the ethanol extract of S. ovata leaves had a flavonoid content of 38,248 ± 0.142 mgQE/gram. In measuring antioxidant activity using the DPPH and ABTS methods, the IC50 values were 31.785 ± 0.047 ppm and 28.303 ± 0.558 ppm, respectively. Based on these results, the ethanol extract of S. ovata provided very strong antioxidant activity with an IC50 value of less than 50 ppm.